ANALISIS PENERAPAN STRATEGI PEMBELAJARAN AFEKTIF DALAM MENANAMKAN PENDIDIKAN KARAKTER PADA PESERTA DIDIK KELAS IV SDN 18 AMPENAN - Meilasari, Yuni Ros; Zohri, Zohri; Jemi, Agustina Yosa; Najwa, Anisa Lailatun; Zulianiy, Astiana; Murniati, Asty; Istiningsih, Siti (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the implementation of affective learning strategies in instilling character education among fourth-grade students at SDN 18 Ampenan. This research employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The findings reveal that affective learning strategies were applied using two main approaches: modeling (providing examples) and habituation (habitual practice). These strategies effectively shaped students’ character, particularly in the aspects of religiosity, nationalism, independence, cooperation, and integrity. The main challenges faced by teachers stem from external factors, such as family environment and peer influence outside of school. Therefore, collaboration between educators and parents is essential to the success of character education. Affective learning strategies prove to be a relevant and contextual approach to building students’ character from an early educational stage.